Kecerdasan Emosi Anak Usia Dini dapat Mempengaruhi Pendidikan Agama Islam Pada Usia Remajanya - Asep Andi Rahman; Imas Masripah (Jurnal al-Thullab, 2021)
Every early childhood must experience various stages of development in his life, from several kinds of development, one of which is the aspect of emotional intelligence. Modern times like today have an impact on the decline in children's awareness to control their emotional intelligence. Thus, controlling children's emotional intelligence must be taught fasting from an early age. In addition, children are also directed to stimulate their emotional intelligence. This study was conducted to determine whether children who are able to increase their emotional intelligence from an early age can influence Islamic religious education in their teens. The purpose of this study was to determine how effective the implementation process of increasing emotional intelligence in early childhood affects Islamic religious education at the age of teenagers. This research uses a qualitative descriptive method with a case study approach. The data collection technique used is the method of observation, interviews and documentation. The research method uses a triangulation technique, namely an approach to the teacher and field observations. The results of this study, that in an effort to increase the emotional intelligence of early childhood physiologically, then when a teenager will be seen the level of honesty, responsibility, visionary, discipline, cooperate with teachers, parents and friends, and he has behaved fairly and cares about the call. the teacher. When he was a teenager he would diligently fast without being asked and he would easily achieve his goals. Setiap anak usia dini pasti mengalami berbagai tahapan pada perkembangan dalam hidupnya, dari beberapa macam perkembangan salah satunya adalah aspek kecerdasan emosional. Zaman modern seperti saat ini berdampak pada menurunnya kesadaran anak untuk mengendalikan kecerdasan emosionalnya. Sehingga, mengontrol kecerdasan emosional anak harus diajarkan puasa sejak dini. Selain itu anak juga diarahkan untuk menstimulus kecerdasan emosionalnya. Penelitian ini dilaksanakan untuk mengetahui apakah anak yang mampu meningkatkan kecerdasan emosinya sejak usia dini dapat mempengaruhi Pendidikan Agama Islam pada usia remajanya. Tujuan penelitian ini adalah untuk mengetahui seberapa efektif proses pelaksanaan meningkatkan kecerdasan emosi anak usia dini yang mempengaruhi Pendidikan Agama Islam pada usia remajanya. Pada penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah metode observasi, wawancara dan dokumentasi. Metode penelitian dengan teknik triangulasi yakni pendekatan ke guru dan pengamatan di lapangan. Hasil penelitian ini, bahwa dalam upaya meningkatkan kecerdasan emosi anak usia dini secara fisiologis, maka ketika remaja akan terlihat tingkat kejujuran, tanggungjawab, visioner, disiplin, bekerjasama dengan guru, orang tua dan teman-temannya, serta ia telah berperilaku adil dan peduli terhadap seruan gurunya. Ketika remaja ia akan rajin berpuasa tanpa disuruh dan ia akan dengan mudah mencapai cita-citanya.